2022
DOI: 10.1021/acscatal.2c03650
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Roles of Hydroxide in CO2 Electroreduction on a Cu Electrode for Achieving Variable Selectivity

Abstract: Hydroxide-derived copper (OH/Cu) electrodes exhibit excellent performance for the electrocatalytic CO2 reduction reaction (CO2RR). However, the role of hydroxide (OH) in CO2RR remains controversial; therefore, the origin of the selectivity enhancement emerging on OH/Cu has not been fully understood. In the present work, we quantitatively evaluated surface OH by electroadsorption and established a direct correlation between the OH amount and selectivity for the production of CH4 and C2+ on OH/Cu with the help o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The bending peak of adsorbed water decreased with the anodic pulse and increased under the cathodic conditions. This phenomenon was possibly related to the local changes of the adsorbed OH species . The OH species played an important role in controlling CO 2 RR products, which also impacted the local pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bending peak of adsorbed water decreased with the anodic pulse and increased under the cathodic conditions. This phenomenon was possibly related to the local changes of the adsorbed OH species . The OH species played an important role in controlling CO 2 RR products, which also impacted the local pH.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was possibly related to the local changes of the adsorbed OH species. 42 The OH species played an important role in controlling CO 2 RR products, which also impacted the local pH. Therefore, we employed the in situ Raman experiment to explore the local pH (Figures S32 and S33).…”
Section: Journal Of Thementioning
confidence: 99%
“…Recent results show that hydroxide-derived copper electrodes exhibit excellent performance in the electrocatalytic CO 2 reduction reaction. 56 Based on the OH/Cu ratio in the electrode, excellent faradaic efficiencies for CH 4 (78%) or C 2+ products (71%) are observed. Most mechanistic indications and factors determining the surface path are invalid for these electrocatalysts.…”
Section: Co 2 Reduction and The Reaction Mechanismmentioning
confidence: 98%
“…There is often a drastic reconstruction during electrocatalysis not corresponding to a change in the behaviour as expected from these mechanistic indications. 326 Sun et al 56 showed that hydroxide-derived copper (OH/Cu) electrodes are active in CO 2 methanation. Copper phosphate nanosheets also offer high performances.…”
Section: From Thermal To Electro-catalysismentioning
confidence: 99%
“…Different catalysts such as Cu-based electrocatalysts, noble metals, and their derived electrocatalysts have been reported for CO 2 electro-reduction. [6][7][8] Recently, a new class of twodimensional (2D) transition metal (TM) carbides, nitrides and carbonitrides (collectively known as MXenes) have remarkable potential applications in numerous electrochemical processes. [9][10][11][12][13][14][15][16] The special metallic electronic structure will give rise to effective electron transport, and the abundant TM atoms with empty d-orbitals are benecial for the activation of gasphase molecules; thus, MXenes have attracted considerable attention in recent years.…”
Section: Introductionmentioning
confidence: 99%